Physiology, metabolism, antibiotic resistance, and genetic diversity of Harveyi clade bacteria isolated from coastal mariculture system in China in the last two decades - Kang, Hao; Yu, Yongxiang; Liao, Meijie; Wang, Yingeng; Yang, Guanpin; Zhang, Zheng; Li, Bin; Rong, Xiaojun; Wang, Chunyuan (Frontiers in Marine Science, 2022)
Vibrio bacteria, especially members of Harveyi clade, are the most important pathogen in aquatic organisms and cause significant economic losses in the world. However，it remains a challenging task to provide more defined taxa of Harveyi clade for biological research and prevention strategies . In the present study, extensive phenotypic, antibiotic resistance, phylogenetic and molecular typing of 192 Harveyi clade isolates with typical interannual difference from coastal area in China were analyzed, which indicated that these Harveyi clade isolates possess significant interspecific genetic and antibiotic resistance diversity. Based on MLSA (gyrB-pyrH-recA-atpA), 192 Harveyi clade isolates were rapidly and accurately classified as 10 species. The Harveyi clade isolates population was composed of 95 sequence types (STs), of which 92 STs were newly identified, displaying high degree of genetic diversity. Among all newly identified ST types, ST327 occupied 11.5% (22/192) of the total number of isolates, which ranked the first and followed by ST215 (which accounts for 6.25%) and 63 STs contained single isolates. At the metabolic level, the results of physiological and biochemical experiments showed that all Harveyi clade isolates were positive for oxidase and negative for melibiose. Antibiotic resistance evaluation indicated that Harveyi clade isolates showed different tolerance to 11 antibiotics. All isolates were unsensitive to neomycin (192/192), and All isolates were unsensitive to neomycin (192/192), and the percentage of resistant strains to sulfadimidine (61/192), sulfadiazine (44/192), sulfamonomethoxine (44/192), sulphamethoxazole (33/192), thiamphenicol (34/192), ciprofloxacin (52/192) and enrofloxacin (31/192) was 31.77%, 22.92%, 22.92%, 17.19%, 17.71%, 27.08 and 16.15%, respectively. 61.8% Harveyi clade isolates had multiple antibiotic resistance index (MARI) lower than 0.1, indicating the risk of antibiotic resistance transmission of most Harveyi clade is low in mariculture systems in China. These results provide substantial data support for further study on the identification and genetic and metabolic diversity of Harveyi clade isolates in mariculture systems in China.